Minat Siswa terhadap Pembelajaran Penjas SMAN 1 Karang Bahagia pada Pertemuan Tatap Muka - Andreas Barnes; Ruslan Abdul Gani; Abdul Salam Hidayat (Journal on Education, 2023)
This study aims to determine students' interest in learning at SMAN 1 Karang Bahagia in face-to-face meetings. The type of approach in this study is a quantitative descriptive approach using survey research methods. The population in this study was class XI students of SMAN 1 Karang Bahagia. The research sample consisted of 84 students using the Simple Random Sampling technique. Data collection techniques in the form of observations and interviews using questionnaires behind closed doors. Data processing techniques using the Microsoft Excel program. The results of this study show that Students' Interest in Learning at SMAN 1 Karang Bahagia in Face-to-Face Meetings is Low with the most frequency considerations being in the Low category as many as 26 students or 31%. Furthermore, in the very high category as many as 6 students or 7%, in the high category as many as 25 students or 30%, the medium category as many as 23 students or 27%, and in the very low category as many as 4 students or 5%.